What Type of Differential Equation Is This?

Calculus Level 5

e y = d y d x + 1 e^y=\frac{dy}{dx}+1

Given that y ( 0 ) = 2 y(0)=-2 , find the equation of the oblique asymptote of y y in the form y = m x + n y=mx+n . Enter m n mn .


The answer is 1.854586542.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Mark Hennings
May 17, 2018

Writing z = y + x z = y+x we have d z d x = e z x \frac{dz}{dx} \; = \; e^{z-x} so that e z d z d x = e x e^{-z} \frac{dz}{dx} \; = \; e^{-x} and hence e z = e x + c e^{-z} = e^{-x} + c Since y ( 0 ) = 2 y(0)=-2 , we deduce that c = e 2 1 c = e^2-1 , and so e y = 1 + ( e 2 1 ) e x y x + ln ( e 2 1 ) \begin{aligned} e^{-y} & = \; 1 + (e^2-1)e^x \\ -y & \approx \; x + \ln(e^2-1) \end{aligned} so that m = 1 m=-1 and n = ln ( e 2 1 ) n = -\ln(e^2-1) , making the answer ln ( e 2 1 ) = 1.854586542 \ln(e^2-1) = \boxed{1.854586542}

Raymond Chan
May 17, 2018

This could be solve in the traditional way:

d y d x = e y 1 \frac{dy}{dx}\; = \; e^{y}-1 d y e y 1 = d x \frac{dy}{e^{y}-1}\; = \; dx

Now integral the right side we can get x, but for the left side, we need to do the following u-substitution:

Let u = e y 1 u=e^{y}-1 , d u = e y d y du=e^{y}dy , d y = d u e y = d u u + 1 dy=\frac{du}{e^{y}}\; = \frac{du}{u+1}

Therefore the equation becomes d u u ( u + 1 ) = d x \frac{du}{u(u+1)}\; = \; dx

Applying Praction Fraction, we get 1 u 1 u + 1 d u = d x \frac{1}{u}-\frac{1}{u+1}\ du = \; dx

Integrate both side, we have l n u u + 1 = x + C ln\frac{u}{u+1}=x+C

Substitute u = e y 1 u=e^y-1 , and simplify a bit, we get l n ( 1 e y ) = x + C ln(1-e^{-y})=x+C

By putting x = 0 x=0 and y = 2 y=-2 , we can easily see C = l n ( 1 e 2 ) C=ln(1-e^2)

Therefore, l n ( 1 e y ) = x + l n ( 1 e 2 ) = l n [ ( 1 e 2 ) e x ] ln(1-e^{-y})=x+ln(1-e^2)=ln[(1-e^2)e^x]

Keep simplifying, we finally get e y = 1 ( 1 e 2 ) e x e^{-y}=1-(1-e^2)e^x

y = l n [ 1 ( 1 e 2 ) e x ] y=-ln[1-(1-e^2)e^x]

Now we start to find out m m and n n to answer the question:

m = l i m x l n [ 1 ( 1 e 2 ) e x ] x m=lim_{x \to \infty} \frac{-ln[1-(1-e^2)e^x]}{x}

Applying L'Hospital Rule, we get m = l i m x ( 1 e 2 ) e x 1 ( 1 e 2 ) e x = l i m x [ 1 ( 1 e 2 ) e x 1 1 ( 1 e 2 ) e x ] = l i m x [ 1 + 1 1 ( 1 e 2 ) e x ] = 1 m=lim_{x \to \infty} \frac{(1-e^2)e^x}{1-(1-e^2)e^x}=lim_{x \to \infty} [-\frac{1-(1-e^2)e^x-1}{1-(1-e^2)e^x}]=lim_{x \to \infty} [-1+\frac{1}{1-(1-e^2)e^x}]=-1

Now solve for n n :

n = l i m x [ l n [ 1 ( 1 e 2 ) e x ] + x ] = l i m x l n e x 1 ( 1 e 2 ) e x = l n [ l i m x e x 1 ( 1 e 2 ) e x ] n=lim_{x \to \infty} [-ln[1-(1-e^2)e^x]+x]=lim_{x \to \infty} ln\frac{e^x}{1-(1-e^2)e^x}=ln [lim_{x \to \infty} \frac{e^x}{1-(1-e^2)e^x}]

Notice that we don't have to re-comput the limit since this limit is almost the same as the limit with m, just a factor of 1 e 2 1-e^2 off.

Therefore, n = l n 1 1 e 2 = l n ( e 2 1 ) n=ln \frac{-1}{1-e^2}=-ln(e^2-1)

Finally, m n = ( 1 ) ( l n ( e 2 1 ) ) = l n ( e 2 1 ) = 1.854586542 mn=(-1)(-ln(e^2-1))=ln(e^2-1)=\boxed{1.854586542}

P.S. What Type of Differential Equation IS This? This is a Separable First-order Differential Equation :)

Nick Turtle
May 17, 2018

e y = d y d x + 1 y = ln ( d y d x + 1 ) \begin{aligned} e^y&=\frac{dy}{dx}+1\\ y&=\ln\left(\frac{dy}{dx}+1\right) \end{aligned}

Now, differentiate both sides and substitute v = d y d x v=\frac{dy}{dx} : d y d x = d 2 y d x 2 1 d y d x + 1 v = d v d x 1 v + 1 v ( v + 1 ) = d v d x \begin{aligned} \frac{dy}{dx}&=\frac{d^2y}{dx^2}\cdot\frac{1}{\frac{dy}{dx}+1}\\ v&=\frac{dv}{dx}\cdot\frac{1}{v+1}\\ v\left(v+1\right)&=\frac{dv}{dx} \end{aligned}

Now, this is simply a separable differential equation. Solve it to find out that v = C e x 1 + C e x v=\frac{Ce^x}{1+Ce^x}

Integrate this to get that y = D ln ( 1 + C e x ) y=D-\ln\left(1+Ce^x\right)

Substitute this into the original equation to see that D = 0 D=0 . In addition, since y ( 0 ) = 2 y(0)=-2 , C = e 2 1 C=e^2-1 : y = ln ( 1 + ( e 2 1 ) e x ) y=-\ln\left(1+\left(e^2-1\right)e^x\right)

To find the oblique asymptotes y = m x + n y=mx+n for some function f ( x ) f(x) , use the following formulas (where a a is one of \infty or -\infty ): m = lim x a f ( x ) x n = lim x a ( f ( x ) m x ) \begin{aligned} \displaystyle m&=\lim_{x\to a}\frac{f(x)}{x}\\ n&=\lim_{x\to a}\left(f(x)-mx\right) \end{aligned} (These formulas basically state that m m is the slope of the function f ( x ) f(x) as x ± x\to\pm\infty , and the y-intercept n n is the difference between f ( x ) f(x) and m x mx as x ± x\to\pm\infty .)

to get that m = 1 , n = ln ( e 2 1 ) m=-1,n=-\ln\left(e^2-1\right) . Thus, m n = ln ( e 2 1 ) mn=\ln\left(e^2-1\right) .

@Nick Turtle I proceeded like Mark Hennings........but, could you justify that why the given formulas work for finding the oblique asymptotes?? Can they work for any function??

Aaghaz Mahajan - 3 years ago

Log in to reply

Those formulas work for any function that has oblique asymptotes. If you look closely (use l'Hôpital's rule), the formula for m m is basically finding the slope of f ( x ) f(x) when x ± x\to \pm \infty . Then, the y-intercept of the oblique asymptote equation n n is the difference between m x mx and f ( x ) f(x) as x ± x\to \pm \infty .

Nick Turtle - 3 years ago

Log in to reply

@Nick Turtle Oh!! I realize it now!! Thanks a lot...!!

Aaghaz Mahajan - 3 years ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...